Comparação, em mulheres inférteis, de teste de avaliação psicológica com a análise psicanalítica clássica - Oliveira, J. B A; Silva, P. G.; Achě, R. S. [UNESP]; Baruffi, R. L R; Mauri, A. L.; Petersen, C. G.; Felipe, V.; Franco, J. G. (My University, 2004)
This study aims to compare a psychological evaluation test to classical psychoanalysis in infertile women. Two hundred women were submitted to the Psychological Evaluation Test (PET). The sum of the scores for the responses ranged from 15 to 60 points, with scores ≥ 30 points being defined as psycho-emotional maladjustment (cut-off point: median + 25%). For comparison, a psychologist submitted the patients to a psychological examination simultaneously, who was unaware of the PET results. From the 200 patients, 66 (33%) presented a test with ≥ 30 points (psycho-emotional maladjustment) and 134 (67%) a test with < 30 points (normal). Upon psychological examination, 105 (52.5%) presented an abnormal evaluation and 95 (47.5%) a normal evaluation. For the PET, statistical analysis showed 82% efficiency, 62% sensitivity, 98% positive predictive value, 99% specificity, 70% negative predictive value, likelihood ratio for a positive test result 62, and likelihood ratio for negative test result 0.38. The PET proved to be a useful clinical instrument, being of help for the selection of patients with psychological needs induced by infertility.
Comparison of the psychological evaluation test and classical psychoanalysis in infertile women
Keywords: Infertility; Psychological evaluation; Psychological test; Score; adult; clinical examination; comparative study; controlled study; diagnostic value; emotional disorder; female; female infertility; human; major clinical study; psychoanalysis; psychologic assessment; scoring system; sensitivity and specificity; statistical analysis; statistical model